Problems of Formation and Realization of Innovative Systems of Hotel and Restaurant Business - Nadiia Sapelnikova; Olena Nykonchuk (Ресторанний і готельний консалтинг: Інновації, 2018)
Actuality. Many factors, both positive and negative, influence on the formation of an effective national innovation system as a complex of legal, financial and social institutions that provide innovative processes. In the modern globalized world, national innovation systems depend on a large extent on the political situation in the world and the cultural characteristics of each country. Creation and dissemination of fundamentally new technologies, products and services is becoming increasingly relevant. Purpose and methods. The aim of the study is to analyze the formation and implementation of national innovation systems in different countries all around the world, the introduction of innovative practices in the hotel industry, the definition of the features of state innovation policy, as well as factors that have a positive or negative impact on the national innovation system. The following methods have been used to solve the research tasks: historiographical, comparative, methods of analysis and synthesis. Results. The results of the study have showed that national innovation systems have been increasingly developing and improving, because the modern economy is characterized by its innovativeness. The most advanced are the innovative systems in the United States and European countries. As for the introduction of innovative practices in the hotel industry, the championship belongs again to the US, the European countries, Japan. Conclusions and discussion. On the basis of the analysis of national innovation systems, we can conclude that under current conditions, the innovation system needs constant improvement. The successful development of the national innovation system is supported by a clear strategy of state policy in the field of innovation; rational use of existing innovation potential; strengthening cooperation between the research and the private sector; introduction of best international experience.